Diversity of Echinoderms in Paranti Beach, Tabang Village, Rainis District, Talaud Islands Regency, North Sulawesi Province - Lalombombuida, Subrita Lalombombuida; Langoy, Marnix; Katili, Deidy Y. (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2019)
This study aims to analyze the diversity of Echinoderms in Paranti Beach, Rainis District, Talaud Islands Regency, North Sulawesi Province. The method used was purposive random sampling and quadrat plot of 20 plots measuring 1m x 1m. Data analysis used diversity index Shannon and Wienner, value index, density, frequency and dominance index. The results of the study were found on the coast of Parantin Beach, namely; 27 species from 4 classes of Echinodermata which include the class Asteroidea (starfish), Echinodea (sea urchins), the class Holothuroidea (Teripang) and the class Ophioroidea (Star snake). Diversity index value on the coast of Paranti, namely at Station I (0.40); Station II (1.56) and at Station III (1.50). This number shows that the diversity of Echinoderms in Paranti Beach at Station I is relatively low and that for Station II and III are abundant. Keywords: Diversity, Echinodermata, Talaud Islands Regency Â ABSTRAK Penelitian ini bertujuan untuk menganalisis keanekaragaman Echinodermata di Pantai Paranti, Kecamatan Rainis, Kabupaten Kepulauan Talaud provinsi Sulawesi Utara. Metode yang digunakan adalah purposive random sampling dan petak kuadrat sebanyak 20 petakyang berukuran 1m x 1m. Analisi data yang digunakan indeks diversitas Shanon dan Wienner, indeks nilai pentinh, Kepadatan, frekuensi dan indeks dominansi. Hasil penelitian ditemukan dipesisir Pantai Parantin yaitu; 27 spesies dari 4 kelas Echinodermata yang termasuk yaitu kelas Asteroidea (bintang laut), Echinodea (Bulu babi), kelas Holothuroidea (Teripang) dan kelas Ophioroidea (Bintang ular). Nilai indeks Keanekaragaman di pantai Paranti yaitu pada Stasiun I (0,40); Stasiun II (1,56) dan pada Stasiun III (1,50). Jumlah ini menunjukan bahwa Keanekaragaman Echinodermata di Pantai Paranti pada Stasiun I tergolong rendah dan untuk Stasiun II dan III sedang melimpah. Kata kunci: Keanekaragaman, Echinodermata, Kabupaten Kepulauan TalaudÂ